Using the analytic hierarchy process to create an erosion risk map. A case study in Malakasiotiko stream, Trikala perfecture - Bathrellos, G.; Skilodimou, H. (Bulletin of the Geological Society of Greece, 2007)
This study is aimed at the evaluation of the erosion risk at the drainage basin of Malakasiotiko stream in Trikala prefecture, using a Geographic Information System (GIS). A database from six factors that influence erosion namely slope, lithology, drainage density, tectonic features density, land use and rainfall inserted into GIS. Each factor was grouped in various classes. A method known as Analytic Hierarchy Process (ΑΗΡ) was applied to rate the individual classes of each factor and weight the impact of one factor against the other in order to determination their importance to erosion process. The results of the ΑΗΡ application in combination with GIS techniques were used to estimate the overall erosion risk and create the erosion risk map. The study area was divided into three zones of erosion risk. High erosion risk zones are mostly located on the northwest, west and south parts of the drainage basin of Malakasiotiko stream. The erosion risk map of the study area can be a useful geologic and géomorphologie criterion for the land use planning.